Pandemics, vulnerability, and prevention: time to fundamentally reassess how we value and communicate risk?: CITIES, HEALTH and COVID-19: Initial reflections and future challenges. (21st July 2021) - Black, Daniel; Bates, Geoff; Gibson, Andy; Hatleskog, Eli; Fichera, Eleonora; Hatchard, Jenny; Md Nazmul, Hasan; Rosenberg, Ges; Larkin, Charles; Brierley, Rachel; Kidger, Judi; Bondy, Krista; et al.
ABSTRACT: For over a decade, pandemics have been on the UK National Risk Register as both the likeliest and most severe of threats. Non-infectious 'lifestyle' diseases were already crippling our healthcare services and our economy. COVID-19 has exposed two critical vulnerabilities: firstly, the UK's failure to adequately assess and communicate the severity of non-communicable disease; secondly, the health inequalities across our society, due not least to the poor quality of our urban environments. This suggests a potentially disastrous lack of preventative action and risk management more generally, notably with regards to the existential risks from the climate and ecological crises.